2011
DOI: 10.3109/10428194.2011.622420
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism correlated with cellular proliferation in diffuse large B-cell lymphoma

Abstract: Standardized uptake value (SUV) is a marker of tumor glucose metabolism detected by [18F]-fluorodeoxyglucose positron emission tomography/computed tomography ((18)F-FDG-PET/CT). The maximum SUV of the whole-body (BmSUV(max)) reflects the tumor aggressiveness in non-Hodgkin lymphoma. To evaluate the correlation between SUV(max) at biopsy site (BxSUV(max)) and proliferation potential of tumor cells in untreated diffuse large B-cell lymphoma (DLBCL), fifteen pre-therapy PET/CT scans in patients with histologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…SUVmax offers a quantitative representation of glucose utilization. This can be a proxy for proliferative rate in DLBCL in vivo 23]. Our study is the first to identify SUVmax ≥15 as a potential predictor of LR in patients with non-bulky disease.…”
Section: Resultsmentioning
confidence: 88%
“…SUVmax offers a quantitative representation of glucose utilization. This can be a proxy for proliferative rate in DLBCL in vivo 23]. Our study is the first to identify SUVmax ≥15 as a potential predictor of LR in patients with non-bulky disease.…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies suggested the association between SUV max and tumor aggressiveness [21][22][23]. And recently, the fact that proliferation potential of tumor cells measured by Ki-67 stain positively correlated with SUV max has been reported [24][25][26][27][28]. However, the measurement of SUV max has confined to the detection of the most obvious metabolic activity of the tumor at single site, but not the overall tumor activity.…”
mentioning
confidence: 99%
“…The F-18 FDG uptake by lymphoma is probably associated with Glut1 expression [25, 26] and Ki-67 values [27, 28]. In many malignant tumors, scan start times of 45–60 min have been reported to cause significant underestimation of the true SUVs, because SUVs do not reach maximum levels until several hours after F-18 FDG injection [2, 23, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we performed ROC analysis without comparing each histological subtype. However, some authors have reported that the SUVmax tended to be lower in Hodgkin’s lymphoma and T-cell lymph nodes than in B-cell lymphoma, with differences observed in the early SUVmax [28]. Examination of a larger number of patients in a prospective study could help in evaluating the role of dual-time-point PET/CT scans in diagnosis of lymphoma.…”
Section: Discussionmentioning
confidence: 99%